Gonad development of the Sulu shrimp, Metapenaeus suluensis Racek and Dall (1965) (Crustacea, Malacostraca Penaeidae) in the Iloilo River, West Central, Philippines - Subong, Kathleen T. Dato-on (University of the Philippines in the Visayas, 2015)
The gonad development of the sulu shrimp Metapenaeus suluensis Racek and Dall (1965) from the Iloilo river were studied over a one-year period from june 2013 to May 2014. Length frequency distribution revealed that both female and male individuals with a length range of 71-90 mm dominated the samples. The sex ration did not differ significantly from 1:1 in all months. Ovarian histology showed four developmental stages namely immature, previtellogenic, vitellogenc and redeveloping. Testicular histology on the other hand, showed five developmental stages namely immature, early maturing, mature, partially spawned and redeveloping. Spent stages were not present in both female and male samples. Females predominated males in all months and in larger length groups. The minimum size at sexual maturity for females is 92mm TL and 81mm TL for males. Gonadosomatic indices (GSI in %) of both sexes showed two maturation peaks whicwas in February to April, the major peak and in September to October, the minor peak. None of female and few male individuals were spawning however, it was assumed that spawning takes place in deeper offshore waters in the months of March to May and September-October. Correlation showed that salinity and surface dissolved oxygen primarily affect growth and maturation of female M. suluensis in the Iloilo River while none of these abiotic parameters affect maturation of male individuals. The higher salinity and lower dissolved oxygen in the months of February to may resulted to an ncrease in gonadal activity in both sexes especially female individuals, while the lowering of salinity and an increase in dissolved oxygen due to monsoon rains during the months of June to January ensures flooding and immigration of post larvae and juveniles from offshore waters to the river, thus immature individuals were present in large numbers. Moreover, results suggest that both female and male M. suluensis exhibits year round gonadal activity and a continuous breeder thus a potential species fro shrimp aquaculture in the Philippines. Based on the results of this study, the river therefore is important t the life cycle of M. suluensis. Future studies must be conducted to verify the identification of other shrimp species within the vicinity of Panay.